2018
DOI: 10.1104/pp.18.00972
|View full text |Cite
|
Sign up to set email alerts
|

A Musashi Splice Variant and Its Interaction Partners Influence Temperature Acclimation in Chlamydomonas

Abstract: ORCID ID: 0000-0003-3414-9850 (M.M.)Microalgae contribute significantly to carbon fixation on Earth. Global warming influences their physiology and growth rates. To understand algal short-term acclimation and adaptation to changes in ambient temperature, it is essential to identify and characterize the molecular components that sense small temperature changes as well as the downstream signaling networks and physiological responses. Here, we used the green biflagellate alga Chlamydomonas reinhardtii as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…One of the resultant clades (‘plants I’) comprises single Arabidopsis ( At1g17640 ) and moss ( Physcomitrella patens ) genes plus duplicated algal ( Chlamydomonas reinhardtii ) and monocot ( Oryza sativa, Sorghum bicolor ) genes. One of the Msi genes from C. reinhardtii (Cre12.g560300.t1.2) has previously been shown to play a role in thermal signalling but phylogenetic analyses in the same study did not identify the second (Cre07.g330300.t1.2) (Li et al, 2018). Although algal genes are not represented in the second clade (‘plants II’), multiple duplications are evident in each of the 5 plant genomes.…”
Section: Resultsmentioning
confidence: 87%
“…One of the resultant clades (‘plants I’) comprises single Arabidopsis ( At1g17640 ) and moss ( Physcomitrella patens ) genes plus duplicated algal ( Chlamydomonas reinhardtii ) and monocot ( Oryza sativa, Sorghum bicolor ) genes. One of the Msi genes from C. reinhardtii (Cre12.g560300.t1.2) has previously been shown to play a role in thermal signalling but phylogenetic analyses in the same study did not identify the second (Cre07.g330300.t1.2) (Li et al, 2018). Although algal genes are not represented in the second clade (‘plants II’), multiple duplications are evident in each of the 5 plant genomes.…”
Section: Resultsmentioning
confidence: 87%
“…CHLAMY1 is a circadian RBP in C. reinhardtii ( Iliev et al, 2006 ). CHLAMY1 C3 subunit interacts with two proteins, XRN1 and Musashi, which cooperate to confer thermal acclimation to C. reinhardtii ( Li et al, 2018 ). In our work, CHLAMY1 C3 subunit, XRN1, and Musashi were all upregulated in C. reinhardtii .…”
Section: Resultsmentioning
confidence: 99%
“…Another relevant clock protein, XRN1, a 5′–3′ exoribonuclease, interacts with the CHLAMY1 subunits ( Dathe et al, 2012 ). According to a recent study, the C3 subunit, XRN1, and Musashi interact with each other and cooperate to confer thermal acclimation to C. reinhardtii ( Li et al, 2018 ). In our analysis, the C3 subunit, XRN1, and Musashi were identified as DEGs in C. reinhardtii consistently with previous studies, but were not differentially regulated in C. nivalis .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of C3 and XRN1 provides a direct integration of temperature and clock regulation, but may also involve other regulatory factors. Li et al (2018) sought to identify other factors working with CHLAMY1 by conducting a coimmunoprecipitation experiment using C. reinhardtii extract and XRN1 as bait. In addition to C3, the authors discovered a number of novel interacting RNA-binding proteins, including one called Musashi.…”
mentioning
confidence: 99%
“…Understanding mechanisms of temperature acclimation is becoming more important with changes in global climate and increases in ocean temperatures. Li et al (2018) have identified a new component in the temperature acclimation system in microalgae through characterization of an alternatively spliced variant, Musashi 60 kD, and have demonstrated its function under physiological conditions. The putative roles of the other Musashi alternatively spliced variants are unknown but common to RNA-binding proteins (Cho et al, 2015).…”
mentioning
confidence: 99%